Pakistan's ''Blue Economy'': Potential and Prospects. (1st January 2014) - ,; ,
Abstract : The idea of ''Blue Economy'' recognizes the seas and oceans as main drivers for the economic development with great potential for innovation and growth. Pakistan is an important maritime state in the Indian Ocean blessed with approximately 1, 050 km long coastline and the Exclusive Economic Zone covering about 240, 000 sq. km. The maritime sector acts as the bedrock of the national economy. To optimally benefit from this natural endowment, there is a need for an integrated National Maritime Policy. Increasing the awareness and knowledge among the decision-makers as well as the general public and capacity building through public-private partnerships are required. Development of effective national compliance mechanism and stimulating renewal of potential maritime sectors through regional and international collaboration can usher the country into an era of significant growth. The efficiency of Pakistani ports should be enhanced by improving the network of rail and road infrastructure. The role of National Co-ordination bodies should be augmented. Impediments are there but efforts can surmount them.